Model Pengembangan Potensi Daya Tarik Wisata Berbasis Masyarakat Di Pantai Petitenget Desa Adat Kerobokan - Saputra, I Gusti Ngurah Alit Dwi; Kadek Ayu Ekasani; Ida Bagus Putra Yadnya (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
The results of the study show that Petitenget Beach has great potential to be developed as a community-based tourism destination, which is reflected in natural and cultural wealth, active community participation, and local and spiritual values. However, the development of this destination faces various challenges, such as limited infrastructure, suboptimal local institutions, and environmental pressures. Based on the SWOT analysis, 16 development strategies were obtained and a community-based management model was formulated that emphasizes collaboration, inclusive empowerment, authentic tourism products, digital promotion, and participatory monitoring. This model aims to harmonize cultural preservation and improve the local economy through active community involvement.